Establishment of short term and long term storage protocols for oil palm (Elaeis guineensis Jacq.) polyembryoids - Palanyandy, Sharrmila Rengeswari (2013)
In vitro culture of oil palm (Elaeis guineensis Jacq.) from suspension culture into plantlet is a time consuming process which has been reported to be highly heterogeneous resulting in embryoids differing in sizes, colours and developmental stages. The ability to select embroids at the right stage of development allows the selection of high quality materials. Due to fact that conversion of embryoids is a continuous process, the establishment of suitable storage method is necessary for the selected material. Thus, this study focus on establishment of short term and long term storage protocols for oil palm polyembryoids. In order to establish a successful storage technique, it is essential to identify the right stage of embryoids prior to plantlet formation which will aid in simultaneous plantlet production whereby it can be stored adequately and recommenced for growth only when needed. In the first experiment, the micromorphological changes during conversion of suspension culture into polyembryoids were observed. Morphological observations revealed that, matured polyembryoids with the presence of globular structures, haustorium and secondary somatic embryo (SSE) as the appropriate stage for rapid conversion into plantlets hence it was chosen for storage. In the second experiment, determination of suitable gelling agent was conducted using two types of gelling agent with different concentration (Agar Type 900 at 8g/L, 10g/L and 12g/L or Gelrite® at 1.5g/L, 2.5g/L and 3.5g/L) for better conversion of selected polyembryoids. Gelrite® with 3.5g/L concentration was chosen as the effective gelling agent for higher conversion of polyembryoids into plantlets. Prior to storage, the samples were pretreated with sucrose to condition the polyembryoids for better adaptation to storage condition. Thus, in the third experiment, the effect of encapsulation and gradual sucrose preculture on polyembryoids was undertaken. Results show that exposure of naked polyembryoids to sucrose preculture led to lethal damage while the encapsulated polyembryoids were able to withstand the treatment and gave better survival. Hence, for both short term and long term storage study, encapsulated and sucrose precultured polyembryoids were used. In the fourth experiment, method for short term storage was established by manipulating storage temperature whereby the samples were stored at 5°C, 10°C and 25°C. In this study, the highest survival (73.3%) was obtained at 5°C after 60 days of storage. The results showed that storage in higher temperature reduced the survival rate due to increasing metabolic activity that denatured the proteins. In the fifth experiment, the encapsulated polyembryoids were subjected to long term storage through cryopreservation method after gradual sucrose preculture and Laminar Air Flow (LAF) desiccation using encapsulation dehydration technique. In this technique, encapsulated materials were subjected to cryopreservation after desiccation in order to avoid freezing injury upon liquid nitrogen (LN) exposure. Based on the results obtained, 73.3% survival percentage was obtained with 23.3% water content for encapsulated polyembryoids that subjected to gradual sucrose preculture and cryopreservation. The experiments showed that, oil palm polyembryoids acquired tolerance for successful storage either short term or long term.